Incident of the historical process in the argentine an educational process (2014)
The article provides an overview and conceptual relationship on the Argentinean education. It presents the beginnings of the educational proposals, the presence of the positivist perspective, legislation on education in the nineteenth century, the university student presence, the incidence of the military dictatorship. A later project of country that tended to the industrial development and the corresponding federal law of education. The methodology used in this article, is to use historical data - without making a history of education - of the formal education process in Argentina in order to sustain the hypothesis that this has been set up on a double strand whose shadow extends up to the present. To achieve this goal and to check this hypothesis are evident: a) as the historical situations, through its thinkers and politicians and their more representative legislation, (B) How these have an impact on the present of the Argentinean educational process, in relation with particular to the primary and secondary level, c) generating a way sociocultural particular being. It is not intended to, therefore, to find a historical novelty; but a different way of reading, raising awareness about how to: a) the political and cultural decisions, B) taken in the past c) have not been harmless, d) What is a lesson for the present. These historical references make visible the struggles that, within the same Argentine society, the sides protagonists were generating. These were primarily religious pro or pro lay; and then these sides became in the federal and unitary, corrupted though, which lasted up to the present, not always in a national easy coexistence.